Race, gender, and image repair theory : how digital media change the landscape - Cole, Hazel James, 1964- (Lexington Books, 2018)
Race, Gender and Image Restoration Theory: How Digital Media Change the Landscape explores themes that are relevant to the socio-political landscape of twenty-first-century America, including race and gender representation, social media and traditional media framing, and image restoration management.